Expression of the prostaglandin F synthase AKR1B1 and the prostaglandin transporter SLCO2A1 in human fetal membranes in relation to spontaneous term and preterm labor - Alzamil, Hana A.; Pawade, Joya; Fortier, Michel A.; Bernal, A. López (Frontiers in Physiology, 2014)
Background: Human labour is a complex series of cellular and molecular events that occur at the materno-fetal and uterine levels. Many hypotheses have been proposed for the initiation of human labour, one hypothesis suggests that maturation of the fetus releases a signal in the amniotic fluid that will be transmitted to myometrium via the fetal membranes and initiate uterine contractions. There is strong evidence that prostaglandins (PGs) play a central role in initiation and progression of human labour. Objectives: In this study we intended to investigate the expression of prostaglandin F synthase and the prostaglandin transporter in the human fetal membranes and to explore the relationship between cytokines and PGs in the mechanism of human labour. Methods: We used fetal membranes obtained before labour at term and after spontaneous labour at term or preterm to identify the changes in prostaglandin F synthase (AKR1B1) and human prostaglandin transporter (SLCO2A1) proteins in relation to parturition. Using fetal membranes explants we tested the effect of cytokines (interleukin-1 and tumour necrosis factor alpha) on PG production and the concomitant changes in cyclooxygenase-2 (PTGS2), AKR1B1 and SLCO2A1 expression. Results: Expression of PTGS2 and AKR1B1 was upregulated in the fetal membranes in association with term labour while SLCO2A1 was downregulated with advancing gestation and during term labour. Before labour, IL-1 increased the expression of PTGS2, however during labour TNF upregulated PTGS2 and AKR1B1 proteins. Conclusions: The prostaglandin F synthase AKR1B1 is upregulated while prostaglandin transporter is downregulated during term labour. The amnion is more responsive than choriodecidua to stimulation with pro-inflammatory cytokines. The mechanisms of term and preterm labour are different.